INTERPRETATION OF JUDGES IN REPRESENTING THE DYNAMICS OF RELIGION OF INDIGENOUS LEGAL INHERITANCE OF BALI - Lilik Mulyadi (Jurnal Hukum dan Peradilan, 2019)
The interpretation of judges in responding to the dynamics of renewal of Balinese inheritance customary law is very dynamic accompanied by the development of justice, especially towards the dimensions of kapurusa as heirs. Originally, kapurusa was only a descendant of men from a male family and adopted sons, and then it expanded to include male status, and eventually included women as heirs. Judges interpreted based on the development of modern law, progressive law, just law with a philosophical and juridical basis starting with the Decision of the MUDP Bali Supreme Court Number 01/KEP/PSM-3/MDP Bali/X/2010 concerning Supreme Court III MUDP Results Bali.